Efeitos dos triterpenos α- e β-amirina e de seus derivados acetilados no sistema nervoso central - Aragão, Gislei Frota (2008)
The mixture of alpha- and beta-amyrin (AMY) triterpenes was isolated from Protium heptaphyllum Aubl March (Burseraceae) which is a medicinal plant common to several Brazilian states and popularly known as “breu branco”. Although the literature presents several studies with these triterpenes, only a few of them emphasizes the CNS, and almost none were performed with triterpene acetylated derivatives. Then, the objectives of the present work were to evaluate, in mice, sedative, anxiolytic, antidepressant and anticonvulsant activities of these drugs, in order to clarify their mechanisms of action. Besides, measurements of monoamines and amino acids by HPLC, in the cortex of mice treated with these drugs, were also performed. The results showed that not only the mixture of alpha- and beta-amyrin (AMY) but also its acetylated derivative (AcAMY) were pharmacologically active and, at some instances, AcAMY was even more efficacious than AMY. In the open field test, AMY and AcAMY, administered acutely or sub-chronically at the doses of 10, 25 and 50 mg/kg, showed a great sedative effect, as indicated by the significant decrease of the exploratory activity (decrease in the number of crossings) as well as the decrease in numbers of grooming and rearing, as compared to diazepam used as a positive control. In the plus maze test, both drugs presented a potent anxiolytic activity indicated by the increase in the number of entrances as well as in the time spent in the open arms. In the forced swimming test, AMY at the doses 2.5 and 5 mg/kg, i.p., increased the immobility time as compared to control and was potentiated by imipramine. In the barbiturateinduced sleeping time, AMY and AcAMY showed a significant increase in parameter analysed, duration of sleep. Furthermore, AMY and its acetylated derivative showed anticonvulsant activities, in the model of PTZ-induced convulsions, but not in two other convulsion models (pilocarpine- and strychnine-induced convulsions). Sedative and anxiolytic activities of AMY were reversed in the presence of flumazenil, a competitive benzodiazepine action inhibitor, an effect similar to that observed with diazepam. In addition, the anticonvulsant effect of AMY was potentiated by polymyxin B and staurosporine, drugs known to inhibit protein kinase C (PKC). Data from cortical monoamine measurements showed significant decreases in noradrenaline and serotonin concentrations, after mice treatments with AMY (1, 2,5 and 5 mg/kg). As far as the amino acid determination is concerned, results showed an increase in taurine and tyrosine levels, and a decrease in glutamate, aspartate and GABA contents, with AMY and AcAMY at the dose of 25mg/kg for seven days. In conclusion, the present study demonstrated anxiolytic, sedative, antidepressant and anticonvulsant actions in AMY and AcAMY, probably involving PKC inhibition and interaction with BDZ receptor. Decreases in monoamines levels, as noradrenaline and serotonin, and amino acid alterations may also play a role.